2009
DOI: 10.1007/s10384-009-0725-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro study of suprachoroidal fibrin glue

Abstract: FG is feasible for suprachoroidal use, and no obvious toxic reaction was observed in either in vitro or in vivo studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The absence of cytotoxic effects in our system is consistent with previous studies that reported the safety of FG when used with the different retinal cell types or implanted into different ocular regions (Robinson and Madison, 2000 ; Pardue et al, 2004 ). However, it should be noted that not all FG is similar, as the use of xenogeneic FG (porcine glue in rabbits with human retinal pigment epithelium cells), caused acute inflammation that resulted in fibrosis (Hou et al, 2009 ). Nevertheless, FG has been successfully used as an adhesive substrate for attachment of peripheral nerve grafts to optic nerve stumps, and is permissive for retinal ganglion cell axon regeneration (Robinson and Madison, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of cytotoxic effects in our system is consistent with previous studies that reported the safety of FG when used with the different retinal cell types or implanted into different ocular regions (Robinson and Madison, 2000 ; Pardue et al, 2004 ). However, it should be noted that not all FG is similar, as the use of xenogeneic FG (porcine glue in rabbits with human retinal pigment epithelium cells), caused acute inflammation that resulted in fibrosis (Hou et al, 2009 ). Nevertheless, FG has been successfully used as an adhesive substrate for attachment of peripheral nerve grafts to optic nerve stumps, and is permissive for retinal ganglion cell axon regeneration (Robinson and Madison, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…6 In another study in rabbits, up to 100 L fibrin glue was injected into the SCS, resulting in minimal toxicity and complications. 14 Preliminary studies have also demonstrated that large biological proteins, such as a human antibody (i.e., bevacizumab), injected into in the SCS in a pig model resulted in no inflammation, whereas a similar dose injected intravitreally resulted in granulomatous vasculitis and vitreitis. 15 Finally, the effectiveness of drug delivery to the SCS was demonstrated in a study in which a sustained-release matrix-reservoir cyclosporine device that was placed in the SCS resulted in long-term control of uveitis in a naturally occurring model of autoimmune uveitis.…”
mentioning
confidence: 97%
“… 9 Hou et al noted fibrin glue as a feasible material to use in the suprachoroidal space, with no obvious toxic reactions observed. 10 The risks from potential vitreous extension of the glue was felt to be minimal and none was observed in our case.…”
Section: Discussionmentioning
confidence: 50%